Perancangan Proses Bisnis Untuk Mengurangi Waste Overproduction dengan Metode Business Process Improvement pada Proses Produksi Konveksi di PT. XYZ - Ananda, Okky (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
PT XYZ is a company engaged in the field of convection. There is a problem related to the excess of the actual production amount of 899 with a production request of 732 which indicates the occurrence of waste overproduction. This research aims to minimize waste overproduction in the production process caused by poor demand management and the process of recording the amount of production every day by workers is done manually so it is necessary to design related records in the information category. Problem solving is done by improving business processes using the Business Process Improvement method. The results of this improvement obtained a proposed business process by making improvements to the initial business process. The process of making google spreadsheet as a recording media is done using the waterfall method. The results of the google spreadsheet design can display the number of requests, cut results, and remaining products continuously so that the recording process can be done more accurately and the collected data will be safely stored in the system so that it can minimize the occurrence of overproduction